Association of self-reported recurrent mild hypoglycemia with incident cardiovascular disease and all-cause mortality in patients with type 2 diabetes: Prospective analysis of the Joint Asia Diabetes Evaluation Registry. Issue 45 (November 2016) - Luk, Andrea On Yan; Ho, Tony S.T.; Lau, Eric S.H.; Ko, Gary T.C.; Ozaki, Risa; Tsang, Chiu-Chi; Kong, Alice P.S.; Ma, Ronald C.W.; So, Wing-Yee; Chow, Francis C.C.; Chan, Juliana C.N.
Abstract : Abstract: Severe hypoglycemia is an established risk marker for cardiovascular complications of diabetes, but whether mild hypoglycemia confers similar risks is unclear. We examined the association of self-reported recurrent mild hypoglycemic events with cardiovascular disease (CVD) and all-cause mortality in a prospective cohort of Chinese adults with type 2 diabetes. From June 2007 to May 2015, 19, 019 patients in Hong Kong underwent comprehensive assessment of metabolic and complication status using the Joint Asia Diabetes Evaluation program. Recurrent mild hypoglycemic event was determined by self-report of mild-to-moderate hypoglycemic symptoms at least once monthly in previous 3 months. Incident cardiovascular events were identified using hospital discharge diagnosis codes and death using Hong Kong Death Registry. Patients reporting recurrent mild hypoglycemia (n = 1501, 8.1%) were younger, had longer disease duration, worse glycemic control, and higher frequencies of vascular complications at baseline. Over 3.9 years of follow-up, respective incidences of CVD and all-cause death were 18.1 and 10.3 per 1000 person-years and 15.4 and 9.9 per 1000 person-years in patients with and without recurrent mild hypoglycemia. Using multivariate Cox regression analysis, recurrent mild hypoglycemia was not associated with CVD or all-cause mortality. In subgroup analysis, mild hypoglycemia was related to CVD in patients with chronic kidney disease (hazard ratio 1.36, 95% confidence interval 1.01–1.84, P  = 0.0435) and those on insulin (hazard ratio 1.37, 95% confidence interval 1.01–1.86, P  = 0.0402) adjusted for confounders. Mild hypoglycemia by self-report was frequent in patients with type 2 diabetes and was associated with increased risk of CVD in susceptible groups.